2020
DOI: 10.1186/s12951-020-00594-6
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of antibacterial and osteoconductive 3D-printed PLGA/Cu(I)@ZIF-8 nanocomposite scaffolds for infected bone repair

Abstract: Background: The repair of large bone defects is a great challenge in clinical practice. In this study, copper-loaded-ZIF-8 nanoparticles and poly (lactide-co-glycolide) (PLGA) were combined to fabricate porous PLGA/Cu(I)@ZIF-8 scaffolds using three-dimensional printing technology for infected bone repair. Methods: The surface morphology of PLGA/Cu(I)@ZIF-8 scaffolds was investigated by transmission electron microscopy and scanning electron microscopy. The PLGA/Cu(I)@ZIF-8 scaffolds were co-cultured with bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(63 citation statements)
references
References 33 publications
0
53
0
Order By: Relevance
“…In addition, implant-related infection is a devastating complication following the application of a medical implant. For example, implant-related infection in orthopedics has become a common problem against the background of a markedly increasing number of implant surgeries being performed [ [92] , [93] , [94] ]. In the United States, implant-related infection is the main cause of total knee arthroplasty, accounting for more than 20% of all cases, and severe infection may lead to amputation [ 95 , 96 ].…”
Section: Antibacterial Activity Of Cu-containing Alloysmentioning
confidence: 99%
“…In addition, implant-related infection is a devastating complication following the application of a medical implant. For example, implant-related infection in orthopedics has become a common problem against the background of a markedly increasing number of implant surgeries being performed [ [92] , [93] , [94] ]. In the United States, implant-related infection is the main cause of total knee arthroplasty, accounting for more than 20% of all cases, and severe infection may lead to amputation [ 95 , 96 ].…”
Section: Antibacterial Activity Of Cu-containing Alloysmentioning
confidence: 99%
“…This implies that the core layer is the leading contributor to the morphology and size distribution of the core-shell fibers. This might be associated with the high electrical conductivity of the core solution 50 . It was reported previously that the sol-gel CL solution (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…With the integration of M/MO nanoparticles, bacterial infection can be avoided during surgical implantation, which otherwise could affect tissue growth, postpone surgical recovery, upsurge risks of complications, and even cause death ( Abudula et al, 2020 ). For example, Zou et al (2020) prepared nanocomposite scaffolds containing poly(lactic-co-glycolic acid) (PLGA), copper/zinc based zeolitic-imidazolate-frameworks (Cu@ZIP-8) by FDM-based 3D printing for infected bone repair application. They suggested that a sustainable release of Cu@ZIP-8 in aqueous media ensures long-term antibacterial efficacy of the developed scaffolds ( Zou et al, 2020 ).…”
Section: Applicationsmentioning
confidence: 99%
“…For example, Zou et al (2020) prepared nanocomposite scaffolds containing poly(lactic-co-glycolic acid) (PLGA), copper/zinc based zeolitic-imidazolate-frameworks (Cu@ZIP-8) by FDM-based 3D printing for infected bone repair application. They suggested that a sustainable release of Cu@ZIP-8 in aqueous media ensures long-term antibacterial efficacy of the developed scaffolds ( Zou et al, 2020 ). Afghah et al (2020) developed a PCL-poly propylene succinate (PCL-PPSu) composite with silver-doped biocidal properties, which can be printable by FDM.…”
Section: Applicationsmentioning
confidence: 99%